KAJIAN BERPERSPEKTIF GENDER TERHADAP PEREMPUAN PEKERJA DI SEKTOR INFORMAL PADA MASA PANDEMI COVID 19 DALAM MEWUJUDKAN KEHIDUPAN YANG LAYAK BERDASAR PASAL 27 (2) UUD 1945 DI KOTA BENGKULU - Noeke Sri Wardhani; Susi Ramadhani; Asep Suherman (UNIB Press, 2021)
During the pandemic, women workers in the informal sector, who were also the primary breadwinners, experienced a double burden, were marginalized and experienced an economic burden; even though they did not give up on the situation, they continued to try to support their families. This paper examines the description and analysis of how women workers in the informal sector work during the Covid 19 pandemic to achieve a decent living for their families and analyzes the factors that affect the income or income of women workers in the informal sector, thus reducing the decent quality of life for their families. Moreover, efforts were made to address the economic recovery of his family. This research is descriptive-explanative with a Feminist Law approach. Data analysis was carried out continuously from the beginning to the end of the study by triangulating data through testing, sorting, categorizing, evaluating, comparing, and synthesizing. The study's results, namely the existence of the Covid 19 pandemic, affected the income or income of women working in the informal sector and reduced the quality of life that was decent for their families. It was proven that all families reduced the budget for daily food and drink needs. Efforts to earn income are carried out in various ways so that they can cover their daily needs. Keywords: Covid-19; Informal; Pandemic; Worker.